Experiencing a Call to Ministry: Changing Trajectories, Re-Structuring Life Stories - Steeves, Kathleen (Qualitative Sociology Review, 2017)
This paper presents a qualitative analysis of women’s experiences of call to Christian pastoral ministry as a second career—a mid-life turning point. Drawing on 44 semi-structured interviews with pastors of different denominations, I look at women’s stories of call through the lens of interpretive theory to analyze how women create meanings around this life altering event, and how they construct past experiences in light of these decisions. I employ George Herbert Mead’s theory of time to analyze how women afford prior secular work experiences sacred meaning in light of their subsequent “pastoral call” experience. This paper attempts to arrive at a better understanding of women’s experience of entering pastoral ministry, as well as their past and future life trajectories.